2016
DOI: 10.1089/vim.2014.0136
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Suppressors of Cytokine Signaling 1 and 3 Is Associated with Arrest of Phosphorylated-STAT1 Nuclear Importation and Reduced Innate Response in Denguevirus-Infected Macrophages

Abstract: To clarify whether the suppressors of cytokine signaling (SOCS) are associated with denguevirus (DENV) evasion of the antiviral response, we analyzed the expression kinetics of SOCS1 and SOCS3 and of the antiviral genes MxA and OAS during DENV infection of U937 macrophages that were or not treated with interferon (IFN)-α. DENV infection produced a viral titer three times higher in untreated than in IFN-α-treated cells (p < 0.001 at 72 h postinfection [p.i.]). Partial inhibition of DENV replication was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In agreement, simultaneous increase of IL-6 and IL-10 in DHF is indicative of the dysregulated immune response that leads to the progress of dengue severity [ 49 ]. The changes in cytokine expression found in this study suggest that deregulation of socs1 and socs3 expression induced by dengue virus infection [ 28 , 29 ] is not just involved in cytokine imbalance but also promotes the persistent inflammatory response that contributes to increased vascular permeability and hemorrhagic manifestations. However, further mechanistic studies are required to clarify how these regulatory factors are altered during dengue infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In agreement, simultaneous increase of IL-6 and IL-10 in DHF is indicative of the dysregulated immune response that leads to the progress of dengue severity [ 49 ]. The changes in cytokine expression found in this study suggest that deregulation of socs1 and socs3 expression induced by dengue virus infection [ 28 , 29 ] is not just involved in cytokine imbalance but also promotes the persistent inflammatory response that contributes to increased vascular permeability and hemorrhagic manifestations. However, further mechanistic studies are required to clarify how these regulatory factors are altered during dengue infection.…”
Section: Discussionmentioning
confidence: 99%
“…socs1 is another negative regulator of cytokine signaling affected by dengue infection [ 28 , 29 ]. Chen et al reported a decrease in socs1 expression in DHF with respect to DF patients, which was associated with low levels of IFN- γ and high levels of IL-10 during defervescence [ 27 ], similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently the viral supernatant was centrifuged for 5 min at 10,000 rpm to remove the cell debris. Aliquots were stored at − 70 °C until use [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%